Winds of change: heterotopias in Nimah Nawwab's The Unfurling - Almahasheer, Muneerah Bader (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper examines a Saudi Arabian poet, Nimah Ismail Nawwab’s collection of poetry, The Unfurling (2004). It suggests that her poetry upend traditional stereotypes of Arab and Saudi women as they demonstrate a relationship between the literal and figurative space and social change, particularly in relation to gender and culture. Thus, they occupy and define what Michel Foucault describes as a heterotopic space - a space that stands apart from others. The creation of the space allows for a new understanding of Arabic culture, particularly in relations to the experiences of women. Through a thematic analysis of the poems, the paper contends that Nawwab’s poems uniquely reflects heterotopia as they document social changes, particularly in relations to gendered shifts in the Saudi Arabian landscape. As women experience transgressive responses to social change around the world, they not only create a space that retains a strong connection to the patriarchal history of the Middle East and the Muslim world, that space in itself is a unique space within a space. Nawwab puts women at the centre of each experience, demonstrating the creation of a larger space for the female self while physically maintaining the same order of the society.